A novel approach to improving the quality of whole-cotyledon tofu by control-released coagulant and the role of fiber - Mengnan Gao; Chunxia Dong; Yanqiu Yuan; Qian Ju; Sibo Zhao; Yayun Hu; Guangzhong Luan (Applied Food Research)
To improve the quality of whole-cotyledon tofu prepared with magnesium chloride as a coagulant, the whole-cotyledon tofu induced by control-release coagulant was prepared, where the ratio of the dehulled soybean to the distilled water was 1:5 (w/w). Effects of control-released coagulant and unfiltered treated on rheological properties, proximate composition, microstructure, and texture of tofu were investigated. The results indicated that the control-release coagulant provided satisfactory application potential, and the temperature of 90 ℃ is favorable to the coagulation process. The use of control-release coagulant improved whole-cotyledon tofu's quality and yield. The results of the approximate composition evaluation showed that in whole-cotyledon tofu there was a 173 % increase in fiber as the okara retained in soymilk, increasing the apparent viscosity and change in the flow behavior of whole-cotyledon soymilk. Confocal laser scanning microscopy (CLSM) confirmed that whole-cotyledon tofu formed a porous and disconnected gel matrix. The overlapped fiber and protein gel matrix might have a positive effect on tofu’ texture. For control-release coagulated tofu, they significantly increased the hardness from 2.42 N to 6 .33N. The study highlights the potential of control-released coagulant to enhance the rheological properties and texture of tofu, thereby contributing to the development of whole-cotyledon products.